1998
DOI: 10.1161/01.hyp.31.1.213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Venular Prostaglandin Release on Arteriolar Diameter During Functional Hyperemia

Abstract: Abstract-Indomethacm treatment or removal of the venular endothehum will attenuate functional artenolar vasodllatlon m the hamster cremaster muscle We tested the hypothesis that prostanold release from venular endothehal cells was responsible for the finctlonal vaso&latlon of the paired artenole The hamster cremaster muscle was prepared for m vlvo nucroscopy and stimulated for 1 mmute (lOV, 40 psec, 1 Hz) Before a second muscle stimulation, the venular endothehum was removed by perfismg the venule with several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 10 publications
4
44
1
Order By: Relevance
“…Similar results were also found in patients with type 2 diabetes (14). Because previous studies have supported a critical role of prostaglandin(s) in mediating functional vasodilation (10,19,20,24,30), it is possible that the impaired functional vasodilation in metabolic syndrome may be due to altered AA metabolism. Indeed, previous studies have shown that urinary thromboxane B 2 excretion is enhanced in 12-wk-old OZRs associated with an increased cyclooxygenase-2 expression in kidney (3,15).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results were also found in patients with type 2 diabetes (14). Because previous studies have supported a critical role of prostaglandin(s) in mediating functional vasodilation (10,19,20,24,30), it is possible that the impaired functional vasodilation in metabolic syndrome may be due to altered AA metabolism. Indeed, previous studies have shown that urinary thromboxane B 2 excretion is enhanced in 12-wk-old OZRs associated with an increased cyclooxygenase-2 expression in kidney (3,15).…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, the role of NO in mediating functional vasodilation in humans and animals is still unclear. Our previous study showed that, in the cremaster muscle, inhibition of cyclooxygenase with indomethacin significantly attenuates functional dilation (19,24), suggesting that prostaglandins play a central role in functional hyperemia (10). Indeed, endothelial-derived prostacyclin (PGI 2 ) has been proposed as playing an important role in regulating local blood flow during exercise through activation of PGI 2 receptors prostacyclin (IP) on vascular smooth muscle cells (20,30).…”
mentioning
confidence: 99%
“…However, two pieces of evidence from these studies would suggest that at least the cyclooxygenase component of the functional response was dependent on an intact venular endothelium. First, in the study by McKay et al (34), disruption of the venular endothelium inhibited the stimulation-induced dilation of the arterioles by ϳ50%. If cyclooxygenase from locations within the tissue other than the venular endothelium were playing a role in the functional hyperemic response, then global administration of indomethacin should further reduce the response to stimulation.…”
Section: Physiological Role For Venular-arteriolar Communicationmentioning
confidence: 98%
“…In these studies, functional hyperemia in the hamster cremaster muscle was inhibited by global administration of the cyclooxygenase inhibitor indomethacin (19,34) or by the phospholipase A 2 inhibitor, quinacrine (39), which blocks the liberation of arachidonic acid from the cell membrane. As these inhibitors were applied to the whole cremaster muscle, it is possible that the arachidonic acid metabolites were coming from locations other than the venular endothelium.…”
Section: Physiological Role For Venular-arteriolar Communicationmentioning
confidence: 99%
“…In addition, when an arteriole is closely paired with a venule, vasoactive substances released from the venule also play an important role in regulating arteriolar diameter, depending on various stimulated conditions such as an increase in venular shear rate (26), an increase in muscle stimulation (16), and an exogenous venular infusion of vasoactive substances (5,11). Nitric oxide (NO), prostaglandins, and adenosine have been implicated as mediators of venule-induced arteriolar dilation.…”
mentioning
confidence: 99%